Gotham Rising : New York in the 1930s. - Stewart, Jules (I.B. Tauris, 2016)
New York is often described as the greatest city in the world. Yet much of the iconic architecture and culture which so defines the city as we know it today from the Empire State Building to the Pastrami sandwich only came into being in the 1930s, in what was perhaps the most significant decade in the city's 400-year history. After the roaring twenties, the catastrophic Wall Street Crash and ensuing Depression seemed to spell disaster for the vibrant city. Yet, in this era, New York underwent an architectural, economic, social and creative renaissance under the leadership of the charismatic mayor Fiorello La Guardia. After seizing power, he declared war on the mafia mobs running vast swathes of the city, attacked political corruption and kick-started the economy through a variety of construction and infrastructure projects --